Analisis Perencanaan dalam Kegiatan Ekstrakurikuler di Madrasah Aliyah Negeri Se-Kabupaten Tanah Datar - Yanti Elvita; Hadriyatul Amni Ali; Adripen Adripen; Asmendri Asmendri (Jurnal Manajemen Pendidikan Islam (MANAPI), 2023)
At the present time education is an aspect of life that has renewal to be discussed because it is a dimension that cannot be separated from the development of human activity as a social being with many reforms in the world of education the need for extracurricular activities to support student achievement which is useful in the future . The diversity of leadership, locations and extracurricular activities at Madrasah Aliyah Negeri throughout Tanah Datar district. This study aims to explain the process of the planning function in the management of extracurricular activities in MAN throughout Tanah Datar regency. This study used a qualitative approach which took place at MANs throughout Tanah Datar Regency. Informants from this study were Madrasah Principals, Deputy Madrasah Heads for Student Affairs and Superintendents of extracurricular activities except for MAN 1 Tanah Datar, only Deputy Head of Madrasahs for Student Affairs because the answers were concurrently Heads of Madrasahs and Extracurricular Advisors . Data collection is done by interview. The data obtained was analyzed with several stages of data reduction, data display and drawing conclusions. Researchers use triangulation of sources and use references in guaranteeing the validity of the data. The findings of the research results can be stated that the implementation of the planning function in the management of extracurricular activities in MAN throughout Tanah Datar Regency has been implemented well in general. However, in some planning processes have not gone well. As in the madrasa forecasting process, it only mentions the objectives of the extracurricular activities carried out, the program implementation strategy, the budget, and policy interpretation